Enxertos cutâneos autólogos e homólogos tratados com plasma rico em plaquetas: estudo experimental em coelhos - Kemper, Bernardo [UNESP] (2015)
The objective of this study was to evaluate clinically and histologically, the effect of PRP on the viability of the autologous and homologous full thickness grafts in rabbits. Four experimental groups (n=9) were studied and designated as G1: autologous graft treated with PRP; G2: autograft; G3: homograft treated with PRP and G4: homograft. Each rabbit was subjected to treatment with PRP and its control of autologous and homologous grafts, representing 36 samples. All steps were documented for the macroscopic clinical assessment and at 19th postoperative days, skin biopsy was collected from the central area, for histomorphological evaluation. The treatment of graft with PRP resulted positive influence in the initial phase or handle of the graft, demonstrated by the reddish macroscopic and cosmetic appearance compared to others treatments. The histomorphometric evaluation, the number of macrophages in the grafts was higher in homologs compared to autologous. However, there was no difference in the number of macrophages and fibroblasts with the PRP treatment. The treatment of the graft with PRP in liquid form, promotes a positive influence on the initial phase or take of the graft